The autonomy of metaphysics: ontology of Kantian tradition in works of analytical philosophers - A. A. Menshikova (Омский научный вестник: Серия "Общество. История. Современность")
The article presents a critical analysis of the influence of I. Kant's ideas on the work of analytical philosophers. It is substantiated the thesis on the independence of Kantian ontology from transcendental epistemology. The article investigated possible areas of integration for various aspects of Kantian ontology and epistemology in the theories of a number of analytical philosophers (P. F. Strawson, W. V. O. Quine), who were directly influenced by I. Kant's ideas. A semantic analysis of the concepts they use does not confirm the hypothesis about the evolutionary influence of Kantian transcendental epistemology on the ontological aspects of the works of analytical philosophers (ontology of language, logical-semantic concepts, notions of proposition and modality, categories of particulars and universals)